2023
DOI: 10.3390/biomedicines11072033
|View full text |Cite
|
Sign up to set email alerts
|

What Nutraceuticals Can Do for Duchenne Muscular Dystrophy: Lessons Learned from Amino Acid Supplementation in Mouse Models

Abstract: Duchenne muscular dystrophy (DMD), the severest form of muscular dystrophy, is characterized by progressive muscle weakness with fatal outcomes most often before the fourth decade of life. Despite the recent addition of molecular treatments, DMD remains a disease without a cure, and the need persists for the development of supportive therapies aiming to help improve patients’ quality of life. This review focuses on the therapeutical potential of amino acid and derivative supplements, summarizing results obtain… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 99 publications
0
5
0
Order By: Relevance
“…Taurine is the most abundant nonessential amino acid in the body [8,16,17]. This nonessential amino acid is mainly present in many foods, particularly seafood, and in lesser amounts in meat [8,19,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taurine is the most abundant nonessential amino acid in the body [8,16,17]. This nonessential amino acid is mainly present in many foods, particularly seafood, and in lesser amounts in meat [8,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…It is one of the few amino acids with a membrane transporter which also has a specific blocker [8,15]. This powerful antioxidant has been reported to block and prevent many pathologies related to the neural, renal, and cardiovascular systems [14,16,17]. Recently, using the UMX-7.1 cardiomyopathic hamster animal model, our group demonstrated that short-term taurine supplementation prevents the development of hypertrophy in males but not in females [18].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in muscle regeneration, there is an increase in taurine, regardless of the type of muscle or genetic etiology of the damage to the fiber, suggesting that metabolic changes are significant indicators of muscle status [ 45 ]. The level of taurine diminishes with advancing age, and reinstating this decline via taurine supplementation protects against age-related muscle mass loss and decreased functionality and also improves both health and lifespan across various species [ 46 48 ]. Its greater concentration in the old group tongue, in this project, suggests the activation of fiber metabolism to prevent muscle degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Glycine supplementation has already been shown to protect against loss of myotubes in nutrient restricted/growth factor restriction models with C2C12 muscle cells in vitro. This in vitro protection has been shown to be dependent on mammalian target of rapamycin complex 1 (mTORC1) signaling [ 63 ] and also a specific glycine activation of mTORC1 involved in muscle regeneration in dystrophic mice [ 48 , 64 ]. Thus, the protection observed in the 1-month-old tongue of the mdx muscle, close to the 20th day degeneration peak, may be related to the high levels of glycine presented in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Of interest is a recent study showing that silencing the receptor activator of the NF-κB ligand (RANKL) alone (and combined with deflazacort) has major benefits for bone health and muscle function, along with reduced myonecrosis and fibrosis in mdx mice [85]. In addition, some nutraceuticals such as amino acids and their derivatives have striking benefits on dystrophic muscles, with decreased myonecrosis, along with reduction of inflammation, oxidative damage, and fibrosis, and are suitable for combination therapies [86]. Glucocorticoids act through multiple mechanisms, although the precise molecular pathways that provide efficacy in DMD (see also discussion in Consideration of 'other effects' of glucocorticoids that may benefit dystrophic muscles section), and those that are responsible for detrimental effects are not fully understood.…”
Section: Benefits Of Steroids Compared With Non-steroidal Anti-inflam...mentioning
confidence: 99%